2016
DOI: 10.3928/01477447-20160222-01
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Plantar Fasciitis: Effect of Platelet-Rich Plasma, Corticosteroid, and Placebo

Abstract: Plantar fasciitis is a common cause of heel pain. It is a disabling disease in its chronic form. It is a degenerative tissue condition of the plantar fascia rather than an inflammation. Various treatment options are available, including nonsteroidal anti-inflammatory drugs, corticosteroid injections, orthosis, and physiotherapy. This study compared the effects of local platelet-rich plasma, corticosteroid, and placebo injections in the treatment of chronic plantar fasciitis. In this double-blind study, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 22 publications
3
103
1
6
Order By: Relevance
“…The platelet-rich plasma (PRP) injections got similar results to the corticosteroids injections, according to the studies of Shetty et al [63] and Aksahin et al [64]. Mahindra et al [62] and Monto et al [61] even showed better outcomes than those obtained with the corticosteroids injection at a mean follow-up of 3 months and 2 years, respectively. Furthermore, there are no evidence of side effects for platelet-rich plasma injection, even if more studies are necessary to optimize the treatment.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The platelet-rich plasma (PRP) injections got similar results to the corticosteroids injections, according to the studies of Shetty et al [63] and Aksahin et al [64]. Mahindra et al [62] and Monto et al [61] even showed better outcomes than those obtained with the corticosteroids injection at a mean follow-up of 3 months and 2 years, respectively. Furthermore, there are no evidence of side effects for platelet-rich plasma injection, even if more studies are necessary to optimize the treatment.…”
Section: Discussionsupporting
confidence: 54%
“…In a randomized controlled single-blinded study, Monto et al [61] found that platelet-rich plasma injection was more effective and durable than corticosteroid injection at 2 years of follow-up. Mahindra et al [62] found that platelet-rich plasma injection had significantly better outcomes compared with corticosteroid injection, based on AOFAS score (American Orthopedic Foot and Ankle Score), at 3 months of follow-up.…”
Section: Platelet Rich Plasmamentioning
confidence: 99%
“…However, the application of autologous PRP in pain management has been well-documented. [27][28][29] Infect, a study done by Mishra et al shows that PRP was superior to bupivacaine in pain relief for patients suffering from elbow tendinopathy. 30 …”
Section: Pain Scorementioning
confidence: 99%
“…Other studies have reported superior results of PRP over corticosteroid therapy. 13,33 A recent study has reported both the therapies to be equally effective. 22 Others also have reported equal efficacy for both PRP and corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However the duration of follow-up was for a longer time; 2 years in one study. 33 Ultrasonographic evaluation is commonly employed for to assess the thickness of the plantar fascia and is of diagnostic significance. 34 The thickness improved in both the groups.…”
Section: Discussionmentioning
confidence: 99%